Geography in their classes riddle , poem and from proverbs of use education educational importance (Journal of Science-Innovative Research in Uzbekistan, 2024)
The use of riddles, poems and proverbs in geography lessons has a great educational value. Poem and proverbs to the students topics in learning motivation will give and their understand increases . And this of students to lessons interest raises and to them knowledge receiver interest and talent creates Geography in their classes poem and proverbs with in education of use important role about Poem and proverbs , geography topics in learning to the students motivation will give and their understand more increases . And this of students to lessons interest raises and to them knowledge receiver interest and talent creates In this way education methodology of students geography science more interesting to the relationship have to be help to give can